Superdense QCD Matter and Compact Stars - Blaschke, David; Sedrakian, David; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This volume covers the main topics in the theory of superdense QCD matter and its application to the astrophysics of compact stars in a comprehensive and yet accessible way. The material is presented as a combination of extensive introductory lectures and more topical contributions. The book is centered around the question whether hypothetical new states of dense matter in the compact star interior could give clues to the explanation of puzzling phenomena such as gamma-ray bursts, pulsar glitches, compact star cooling and gravitational waves.
Compact Stars -- DYNAMIC STABILITY OF COMPACT STARS -- CONSTRAINTS ON SUPERDENSEMATTER FROM X-RAY BINARIES -- POSTGLITCH RELAXATIONS OF ANGULAR VELOCITY OF PULSARS -- ISOLATED NEUTRON STARS: AN ASTROPHYSICAL PERSPECTIVE -- Superdense QCD Matter -- CLUSTERS AND CONDENSATES IN THE NUCLEARMATTER EQUATIONOF STATE -- NUCLEAR EQUATION OF STATE AND THESTRUCTURE OF NEUTRON STARS -- NEUTRON STAR STRUCTURE WITH HYPERONS AND QUARKS -- THE QCD EQUATION OF STATE AND QUARK STAR PROPERTIES -- EFFECTIVE LAGRANGIANS FOR QCD: DUALITY AND EXACT RESULTS -- COLOR SUPERCONDUCTIVITY AND HIGH DENSITY EFFECTIVE THEORY -- COLOR SUPERCONDUCTING QUARK MATTERAND THE INTERIOR OF NEUTRON STARS -- SUPERCONDUCTIVITY WITH DEFORMED FERMI SURFACES AND COMPACT STARS -- NEUTRAL DENSE QUARK MATTER -- POSSIBILITY OF COLOR MAGNETIC SUPERCONDUCTIVITY -- MAGNETIC FIELDS OF COMPACT STARS WITH SUPERCONDUCTING QUARK CORES -- THERMAL COLOR-SUPERCONDUCTING FLUCTUATIONS IN DENSE QUARK MATTER -- THE INNER STRUCTURE OF HYBRID STARS -- Signals for Superdense QCD Matter in Compact Stars -- GAMMA-RAY BURSTS AND THEIR CENTRAL ENGINES -- SUPERDENSE STARSWITH A QUARK CORE -- DIQUARKCONDENSATION EFFECTSON HOT QUARK STAR CONFIGURATIONS -- GAMMA RAY BURSTS AND DELAYED QUARK-DECONFINEMENT -- COLOR SUPERCONDUCTING QUARK MATTER AND COMPACT STAR OBSERVABLES -- LOOKING INSIDE THE EARTHWITH SOLARAND SUPERNOVA NEUTRINOS: AN ANALYTIC APPROACH -- DECONFINEMENT PHASE TRANSITION IN RELATIVISTIC NEUTRON STAR MERGERS.
Keywords: PHYSICS; ASTROPHYSICS; RELATIVITY (PHYSICS).; NUCLEAR PHYSICS; QUANTUM THEORY; SUPERCONDUCTIVITY; PHYSICS; ASTROPHYSICS; ELEMENTARY PARTICLES, QUANTUM FIELD THEORY; NUCLEAR PHYSICS, HEAVY IONS, HADRONS; RELATIVITY AND COSMOLOGY; SUPERCONDUCTIVITY, SUPERFLUIDITY, QUANTUM FLUIDS